2021
DOI: 10.3390/geosciences11030139
|View full text |Cite
|
Sign up to set email alerts
|

Active Fault Systems in the Inner Northwest Apennines, Italy: A Reappraisal One Century after the 1920 Mw ~6.5 Fivizzano Earthquake

Abstract: Based on the review of the available stratigraphic, tectonic, morphological, geodetic, and seismological data, along with new structural observations, we present a reappraisal of the potential seismogenic faults and fault systems in the inner northwest Apennines, Italy, which was the site, one century ago, of the devastating Mw ~6.5, 1920 Fivizzano earthquake. Our updated fault catalog provides the fault locations, as well as the description of their architecture, large-scale segmentation, cumulative displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Fazzini & Gelmini, 1982;Bemporad et al 1986;Liotta, 1991;Pascucci et al 2007) and their impact in controlling low-magnitude earthquakes has also been highlighted for northern Tuscany (e.g. Molli et al 2021). Many of these 'lineaments' are ascribed to the presence of lithotypes, which react differently to erosion, as could be the case of the 'Piombino-Faenza line'.…”
Section: Discussionmentioning
confidence: 99%
“…Fazzini & Gelmini, 1982;Bemporad et al 1986;Liotta, 1991;Pascucci et al 2007) and their impact in controlling low-magnitude earthquakes has also been highlighted for northern Tuscany (e.g. Molli et al 2021). Many of these 'lineaments' are ascribed to the presence of lithotypes, which react differently to erosion, as could be the case of the 'Piombino-Faenza line'.…”
Section: Discussionmentioning
confidence: 99%
“…During the early stage of D2, crenulation folds with a characteristic subhorizontal axial plane developed on a regional scale, while successive deformation was associated with semibrittle and brittle structures, represented by kink and open folds, as well as low‐angle normal faults (Molli et al., 2018). The final stages of deformation and erosion‐driven unroofing and exhumation are recorded by systems of high‐angle normal to oblique‐normal and transcurrent faults, related with the recent to active deformation regime affecting the area (Molli et al., 2021).…”
Section: Geological Background and Rationalementioning
confidence: 99%
“…The activation of the half-graben dates to the upper Miocene. According to [26], the geological boundaries are defined by the Pisan Mounts (north-east), the Livornesi Mounts (south-east), and the Secche della Meloria (south-west); the north-western limit is yet to be unequivocally identified, but a study by [27] indicated the area of Marina di Massa as the possible northern edge. Presently, the depocenter of the basin (up to 2500 m deep) is located in the area of the Arno River mouth.…”
Section: Physical Setting 21 Geological and Morphological Settingmentioning
confidence: 99%
“…The top hundred meters of the coastal plain subsurface consist of a cyclic alternation of continental and nearshore deposits related to glacial-interglacial cycles, which have ultimately been explained as a series of transgressive-regressive sequences [28][29][30]. On the other hand, the Magra Basin is a graben defined by two structures on the western and eastern sides: respectively, the Punta Bianca horst and the Apuan Alps [26]. Its formation dates to the Pliocene and is related to high-angle normal faults, located and still visible in the area of the Punta Bianca headland [26,31,32].…”
Section: Physical Setting 21 Geological and Morphological Settingmentioning
confidence: 99%
See 1 more Smart Citation